Thermal oxidation of oxynitride films as a strategy to achieve (Sr2Ta2O7)100-x(La2Ti2O7)x based oxide perovskite films with x = 1.65. Issue 16 (December 2020) - Le Gendre, L.; Le Paven, C.; Haydoura, M.; Benzerga, R.; Marlec, F.; Sharaiha, A.; Cheviré, F.; Tessier, F.; Moréac, A.
Highlights: Sputtering deposition of films of the (Sr2 Ta2 O7 )100-x (La2 Ti2 O7 )x solid solution. Strontium deficient tetragonal tungsten bronze oxide films deposited under dioxygen. Stoichiometric perovskite oxynitride films under dinitrogen. Annealings of oxynitride films under air from 450 to 1000°C. Tunable intermediate phases containing nitrogen-nitrogen pairs in an oxide matrix. Abstract: This study concerns STLTO compounds of the ferroelectric (Sr2 Ta2 O7 )100-x (La2 Ti2 O7 )x solid solution. The purpose is to produce the STLTO composition x = 1.65 as thin films by thermal oxidation of the corresponding oxynitride composition. Indeed, the combination of an STLTO oxide target with a dioxygen-rich reactive atmosphere during the sputtering deposition leads to Sr-deficient oxide thin films, shifting composition and structure from the perovskite to the tetragonal tungsten bronze type. An alternative synthesis pathway is to first deposit, under nitrogen-rich atmosphere, stoichiometric oxynitride films and produce, by thermal annealing under air, the stoichiometric oxide. For low oxidation temperatures ([550–600 °C]), samples remain intact and display an oxide character but still contain a significant amount of nitrogen, they could be described as intermediate phases containing nitrogen-nitrogen pairs as demonstrated by Raman. Dielectric characteristics of these original film materials are of interest with a tunability value of 26 % at 30 kV/cm (10 kHz).